FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMAKAIAN KONTRASEPSI IMPLANT DI PUSKESMAS SIMPANG RAMBUTAN - Eka Rahmawati; Suryani Suryani (Universitas Pahlawan, 2022)
Contraception is an attempt to space pregnancies or plan the number and spacing of pregnancies using contraceptive methods. Implant is a contraceptive device in the form of a small capsule containing the hormone lovonorgestril which is placed under the skin of the inner upper arm. The formulation of the problem in this study was to determine the relationship between Fear of Side Effects, Access to Service Facilities, and Husband's Support with the use of Implant Contraception at the Simpang Rambutan Health Center, Banyuasin Regency in 2021. The research design that will be used in this study is descriptive analytic with a cross sectional approach. The research was carried out in the work area of ​​the Simpang Rambutan Health Center in July-August 2021 with a sample of 32 respondents. The analysis used is the che square test. Univariate analysis results show that of the 33 respondents most of the respondents did not use implant contraceptives, which amounted to 19 respondents (59.4%) and 13 respondents (40.6%). The results of the chi-square statistical test obtained value = 0.011 for the variable fear of side effects, p value = 0.000 for access to health services, p value = 0.002 for husband's support. shows that there is a significant relationship between fear of side effects, husband's support and access to health services with the use of implant contraceptives at the Simpang Rambutan Health Center, Banyuasin Regency in 2021. The suggestions in this study are that it can be used as study material for the puskesmas in order to increase the coverage of implant contraceptive participants. especially in the work area of ​​the Simpang Rambutan Health Center, Banyuasin Regency. Keywords : Implant Contraception, Access to Health Services, Husband's Support.